Jaridon 6, a new diterpene from Rabdosia rubescens (Hemsl.) Hara, can display anti‐gastric cancer resistance by inhibiting SIRT1 and inducing autophagy. (19th August 2021) - Fu, Ling; Han, Bing‐Kai; Meng, Fang‐Feng; Wang, Jun‐Wei; Wang, Tian‐Ye; Li, Hui‐Ju; Sun, Ying‐ying; Zou, Guo‐na; Li, Xiao‐rui; Li, Wen; Bi, Yue‐Feng; Ke, Yu; et al.
Abstract : Tumor resistance is the main cause of treatment failure and is associated with many tumor factors. Jaridon 6, a new diterpene extracted from Rabdosia rubescens (Hemsl.) Hara, which has been previously extracted by our research team, has been tested having more obvious advantages in resistant tumor cells. However, its mechanism is unclear. In this study, we studied the effect and the specific mechanism of Jaridon 6 in resistant gastric cancer cells. Cytotoxicity test, colony test, western blotting, and nude test verified the anti‐drug resistance ability of Jaridon 6 in the MGC803/PTX and MGC803/5‐Fu cells. Jaridon 6 has shown obvious inhibitory effects in the sirtuin 1 (SIRT1) enzyme test. Transmission electron microscopy and immunofluorescence tests further proved the autophagic action of Jaridon 6. Jaridon 6 could inhibit the proliferation of the resistant gastric cancer cell in vivo and in vitro. Jaridon 6 inhibited SIRT1 enzyme and induced autophagy by inhibiting the phosphoinositide 3‐kinase/protein kinase B (PI3K/AKT) pathway. Thus, it may be considered for treating gastric cancer resistance by individual or combined administration, as an SIRT1 inhibitor and autophagy inducer.